Tail Gait : a Mrs. Murphy Mystery - Brown, Rita Mae; Brown, Sneaky Pie, 1982- (Brown, Rita Mae. Mrs. Murphy mystery., 2015)
"In the twenty-third book in the New York Times bestselling mystery series, Rita Mae Brown and her feline co-author Sneaky Pie Brown return with an all-new mystery starring Mary Minor "Harry" Haristeen, intrepid kitty sleuths Mrs. Murphy and Pewter, and Tee Tucker, the ever-faithful crime-solving corgi"--